Odpowiedź :
(a) 8(x-3)(x+5)(2x-7)=o /:8
(x-3)(x+5)(2x-7)=o
x=3 v x=-5 x=⁷/₂
Pierwiastki jednokrotne
(b) (x-3)⁴(x-2)³(x+7)=0
x=3 v x=2 v x=-7
4-krotny, 3-krotny, 1-krotny
(c)5x²(x-1)⁴(x+3)=0
x=0 v x=1 v x=-3
2-krotny, 4-krotny, 1-krotny
(d) (9x-3)(2x-5)(4-x)³=0
x=⅓ v x=⁵/₂ v x=4
1-krotny, 1-krotny, 3-krotny
(x-3)(x+5)(2x-7)=o
x=3 v x=-5 x=⁷/₂
Pierwiastki jednokrotne
(b) (x-3)⁴(x-2)³(x+7)=0
x=3 v x=2 v x=-7
4-krotny, 3-krotny, 1-krotny
(c)5x²(x-1)⁴(x+3)=0
x=0 v x=1 v x=-3
2-krotny, 4-krotny, 1-krotny
(d) (9x-3)(2x-5)(4-x)³=0
x=⅓ v x=⁵/₂ v x=4
1-krotny, 1-krotny, 3-krotny